Bond strength of reinforcement in splices in beams - Turk, K; Yildirim, MS (Techno-Press, 2003)
The primary aim of this study was to investigate the bond strength between reinforcement and concrete. Large sized nine beams, which were produced from concrete with approximately f(c)(')= 30 MPa, were tested. Each beam was designed to include two bars in tension, spliced at the center of the span. The splice length was selected so that bars would fail in bond, splitting the concrete cover in the splice region, before reaching the yield point. In all experiments, the variable used was the reinforcing bar diameter. In the experiments, beam specimens were loaded in positive bending with the splice in a constant moment region. In consequence, as the bar diameter increased, bond strength and ductility reduced but, however, the stiffnesses of the beams (resistance to deflection) increased. Morever, a empirical equation was obtained to calculate the bond strength of reinforcement and this equation was compared with Orangun et al. (1977) and Esfahani and Rangan (1998). There was a good agreement between the values computed from the predictive equation and those computed from equations of Orangun et al. (1977) and Esfahani and Rangan (1998).
Keywords: beams; bond of reinforcing bar-concrete; deformed bar; bending; splice length